Respuesta :
Answer:
a/3 -c =b
Step-by-step explanation:
a=3b+c divide 3 on both sides
a/3 =b+c subtract c on both sides
a/3-c = b
I used to overthink this all the time its easy i promise :)
b=a/3- c/3
Step 1: Flip the equation.
3b+c=a
Step 2: Add -c to both sides.
3b + c + (-c)=a + (-c)
3b=a - c
Step 3: Divide both sides by 3.
3b/3= a - c/3
b=1/3a + -1/3c
Step 1: Flip the equation.
3b+c=a
Step 2: Add -c to both sides.
3b + c + (-c)=a + (-c)
3b=a - c
Step 3: Divide both sides by 3.
3b/3= a - c/3
b=1/3a + -1/3c